Mironenko’s limit test for numerical and power series - Kaida, S.V.; Petrenko, I.V.; Mironenko, L.P. (Искусственный интеллект, 2014)
The report describes the derivation and application of Mironenko’s test for series with positive terms. Mironenko’s test has the same limitations that have d'Alembert's ratio test and Cauchy's radical test. But in practical sense Mironenko’s test has some advantages, moreover, it can be used for power series research.